In de Sloot ... Uit de Sloot : voorstel Gemeentelijke Kunstaankopen 1997. - Bloem, Marja; Folkersma, Nina; Fuchs, Rudi H. (Amsterdam : Stedelijk Museum Amsterdam, 1997)
Baer, Joe ; Beekman, Merina ; Brink, Jasper Van Den ; Draisma, Janica ; Grantsaan, Gillion ; de Gruyter, Voebe ; van Houwelingen, Hans ; Huttenlocher, Britta ; Hurkmans, Rini ; Jungerman, Remy ; Killaars, Fransje ; Kooijmans, Jeroen ; Van Meerendonk, Theo ; Mik, Aernout ; Mooibroek, Sabine ; Onnen, Serge ; de Pals, Anne van ; Raedecker, Michael ; Rouppe van der Voort, Alexandra ; Schaap, Femke ; Scholten, Hans ; Visser, Barbara ; van Warmerdam, Marijke
biografie
In de Sloot ... Uit de Sloot : voorstel Gemeentelijke Kunstaankopen 1997, Stedelijk Museum Amsterdam, 19.12.1997 - 01.02.1998
Nederlands
boek